Genetic Adjuvantation of Recombinant MVA with CD40L Potentiates CD8 T Cell Mediated Immunity - Lauterbach, Henning; Pätzold, Juliane; Kassub, Ronny; Bathke, Barbara; Brinkmann, Kay; Chaplin, Paul; Suter, Mark; Hochrein, Hubertus (Frontiers in Immunology, 2013)
Modified vaccinia Ankara (MVA) is a safe and promising viral vaccine vector that is currently investigated in several clinical and pre-clinical trials. In contrast to inactivated or sub-unit vaccines, MVA is able to induce strong humoral as well as cellular immune responses. In order to further improve its CD8 T cell inducing capacity, we genetically adjuvanted MVA with the coding sequence of murine CD40L, a member of the tumor necrosis factor (TNF) superfamily. Immunization of mice with this new vector led to strongly enhanced primary and memory CD8 T cell responses. Concordant with the enhanced CD8 T cell response, we could detect stronger activation of dendritic cells and higher systemic levels of innate cytokines (including IL-12p70) early after immunization. Interestingly, acquisition of memory characteristics (i.e., IL-7R expression) was accelerated after immunization with MVA-CD40L in comparison to non-adjuvanted MVA. Furthermore, the generated CTLs also showed improved functionality as demonstrated by intracellular cytokine staining and in vivo killing activity. Importantly, the superior CTL response after a single MVA-CD40L immunization was able to protect B cell deficient mice against a fatal infection with ectromelia virus. Taken together, we show that genetic adjuvantation of MVA can change strength, quality and functionality of innate and adaptive immune responses. These data should facilitate a rational vaccine design with a focus on rapid induction of large numbers of CD8 T cells able to protect against specific diseases.